Treatment of the Bleaching Effluent from Sulfite Pulp Production by Ceramic Membrane Filtration - Ebrahimi, Mehrdad; Busse, Nadine; Kerker, Steffen; Schmitz, Oliver; Hilpert, Markus (My University, 2016)
Pulp and paper waste water is one of the major sources of industrial water pollution. This study tested the suitability of ceramic tubular membrane technology as an alternative to conventional waste water treatment in the pulp and paper industry. In this context, in series batch and semi-batch membrane processes comprising microfiltration, ultrafiltration and nanofiltration, ceramic membranes were developed to reduce the chemical oxygen demand (COD) and remove residual lignin from the effluent flow during sulfite pulp production. A comparison of the ceramic membranes in terms of separation efficiency and performance revealed that the two-stage process configuration with microfiltration followed by ultrafiltration was most suitable for the efficient treatment of the alkaline bleaching effluent tested herein, reducing the COD concentration and residual lignin levels by more than 35% and 70%, respectively.
Citation: Ebrahimi, M.; Busse, N.; Kerker, S.; Schmitz, O.; Hilpert, M.; Czermak, P. Treatment of the Bleaching Effluent from Sulfite Pulp Production by Ceramic Membrane Filtration. Membranes 2016, 6, 7.
Keywords: Ceramic Membrane; Bleaching Effluents; Waste Water Treatment; Chemical Oxygen Demand Removal; Membrane Fouling; Permeate Flux Rate